2003
DOI: 10.1105/tpc.015560
|View full text |Cite
|
Sign up to set email alerts
|

ALTERED RESPONSE TO GRAVITY Is a Peripheral Membrane Protein That Modulates Gravity-Induced Cytoplasmic Alkalinization and Lateral Auxin Transport in Plant Statocytes

Abstract: ARG1 ( ALTERED RESPONSE TO GRAVITY ) is required for normal root and hypocotyl gravitropism. Here, we show that targeting ARG1 to the gravity-perceiving cells of roots or hypocotyls is sufficient to rescue the gravitropic defects in the corresponding organs of arg1-2 null mutants. The cytosolic alkalinization of root cap columella cells that normally occurs very rapidly upon gravistimulation is lacking in arg1-2 mutants. Additionally, vertically grown arg1-2 roots appear to accumulate a greater amount of auxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(165 citation statements)
references
References 64 publications
7
151
1
6
Order By: Relevance
“…Reduced PIN2 protein abundance may limit basipetal auxin transport and thereby contribute to the increased auxin activity that we observed at the root tip with the DR5:GUS and DII-VENUS reporters in response to hypoxia. Elevated auxin activity at the root tip has been observed in the pin2 mutant (Boonsirichai et al, 2003). Unlike other pin mutants that do not have an altered root gravitropic response, the pin2 mutant shows weakly agravitropic root growth ) that was also observed in this study.…”
Section: Hypoxia Increases Auxin Activity At the Root Tipsupporting
confidence: 56%
“…Reduced PIN2 protein abundance may limit basipetal auxin transport and thereby contribute to the increased auxin activity that we observed at the root tip with the DR5:GUS and DII-VENUS reporters in response to hypoxia. Elevated auxin activity at the root tip has been observed in the pin2 mutant (Boonsirichai et al, 2003). Unlike other pin mutants that do not have an altered root gravitropic response, the pin2 mutant shows weakly agravitropic root growth ) that was also observed in this study.…”
Section: Hypoxia Increases Auxin Activity At the Root Tipsupporting
confidence: 56%
“…(ARL2), are required for root and hypocotyl gravitropism, influencing the distribution of auxin upon stimulation (Sedbrook et al, 1999;Boonsirichai et al, 2003;Guan et al, 2003). At least ARL2 localizes to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the classic Cholodny-Went theory, recent studies have shown the formation of lateral auxin gradients in Arabidopsis roots upon gravistimulation [64][65][66]. To determine whether the reduced gravity response in pip5k2 is accompanied by an alteration in the asymmetric distribution of auxin in the root tip, GUS activity under gravistimulation was analyzed in WT and pip5k2 seedlings containing the DR5-GUS cassette.…”
Section: Suppressed Redistribution Of Auxin and Pin2 Under Gravistimumentioning
confidence: 99%